PUSAT SENI RUPA DI SURAKARTA DENGAN PENDEKATAN ARSITEKTUR NEO VERNAKULAR - Muhammad Fajar Hafidz; Samsudi Samsudi Samsudi; Titis Srimuda Pitana (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Fine Arts Center with Neo Vernacular Architectural approach is an integrated institution for variety fine arts activities producing two and three dimensional works and the institution are equipped with infrastructure and facility with a design approach that is able to apply cultural, environmental, and local climate elements expressed in a modern architectural building. The underlying reason of the design of Fine Arts Center Building is many art potentials found in Surakarta, but they had no a representative public establishment to promote fine art development of Surakarta. The emerging design problem is how to plan and to design a building of Fine Arts Center in Surakarta by using Neo Vernacular Architectural approach. The Neo Vernacular Architecture is selected as an approach of preserving local architectural elements or characters and combined them with modern ones that are developing at present in order to attract visitors and artists to use the planned fine arst center. Keywords: Fine Arts Center, Neo Vernacular Architecture, Potential and Fine Arts Activities